1995
DOI: 10.1128/jb.177.1.212-221.1995
|View full text |Cite
|
Sign up to set email alerts
|

The hsp70 gene family of Neurospora crassa: cloning, sequence analysis, expression, and genetic mapping of the major stress-inducible member

Abstract: The gene encoding the major heat shock-inducible member of the HSP70 family of Neurospora crassa was cloned and characterized. The 5 nontranscribed region shows the presence of consensus sequence motifs resembling the classical heat shock elements found in many heat shock-responsive eukaryotic promoters, as well as metal-responsive-element sequences. The coding region of the gene contains four introns with boundaries and internal consensus motifs typical of genes of filamentous fungi. None of the other stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…These manipulations were performed in the dark, and then all samples were harvested at the same developmental age and at the same circadian time. For heat-shock analyses, mycelia were incubated in growth medium preheated to 47°C as described previously (16). Osmotic stress was accomplished by transferring mycelia for the indicated times into growth medium containing 4% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…These manipulations were performed in the dark, and then all samples were harvested at the same developmental age and at the same circadian time. For heat-shock analyses, mycelia were incubated in growth medium preheated to 47°C as described previously (16). Osmotic stress was accomplished by transferring mycelia for the indicated times into growth medium containing 4% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…The basic HSE shows similarity across a wide range of organisms and is based around GAA repeats, the spacing and orientation of which vary and may influence which sites are recognized by different HSFs or differently phosphorylated HSFs (20). For Neurospora, HSE are not yet well defined, but nGAAn .. nTTCn motifs (where "n" can be any nucleotide) are present in the promoters of hsp30 (38) and hsp70 (21). Additionally, a factor in Neurospora protein extracts binds specifically to labeled oligonucleotides containing the classic yeast HSF binding sequence nTTCnnGAAnnTTCn (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have reported the presence of four introns in Hsp70 gene of the filamentous fungi N. crassa (Kapoor et al, 1995) and one intron in aquatic fungus Blastocladiella emersonii (Stefani and Gomes, 1995). Introns have been also found in Hsp83 of Drosophila (Holmgren et al, 1979) and Hsp70 of Caenorhabditis elegans (Snutch et al, 1988).…”
Section: Discussionmentioning
confidence: 99%